Спектральний аналіз вібрацій рухомих частин електричних машин - Гижко, Ю.І. (Технічна електродинаміка, 2011)
Experimental research using information-measuring system of diagnosis that uses Bluetooth wireless standard to transmit the measured data. This research received vibration signals measured on moving nodes of the electric machine. The basic mathematical relations underlying the algorithms for determining estimates of the spectral density of the signal. Using the software package performed the spectral analysis of received signals and given plots of spectral power of the measured vibration signal on the frequency.